Impact of body mass index on critically ill COVID-19 patients admitted in a tertiary care hospital : a retrospective observational study - Gupta, Savita; Goel, Varun; Nazir, Nazia; Srivastava, Saurabh; Srivastava, Anurag (Asian Journal of Medical Sciences, 2022)
Background: Increased body mass index (BMI) is a known risk factor for respiratory infection and is being recognized as a predisposing factor in the COVID‐19 pandemic caused by the severe acute respiratory syndrome coronavirus‐2. Aims and Objectives: This study aimed to assess the association between different body mass index categories with severe COVID-19 patients leading to death. Materials and Methods: This retrospective study of six months included the laboratory-confirmed COVID-19 patients admitted to an ICU of a tertiary care academic health care organization. The medical records were reviewed at least 14 days after admission. Results: 484 patients were included, and BMI data were available for 306 patients. 40.19% had a normal weight, 26.79% were overweight, 17.97% had BMI 30-34.9 Kg/m2 and 15.03% had BMI ≥ 35 Kg/m2. Overall, 58 patients (18.95%) died within 14 days of ICU admission, 50.98% were discharged alive or referred from the hospital within 14 days, and 30.06% remained hospitalized at 14 days. After controlling for all covariates, there was a significantly increased risk of mortality in the patients with obesity class I (RR 2.03, 95% CI 1.07-3.85, P = 0.030) and patients with obesity class II & III (RR 2.83, 95% CI 1.54–5.22, P <0.001) compared with those with normal BMI. Conclusions: Obesity was associated with an unfavorable outcome among patients with COVID-19. Patients with obesity should be more closely monitored when hospitalized for COVID-19 as there is increasing evidence of relation of severity of COVID-19 and obesity which appears to be a factor in the health risks.